2004
DOI: 10.1016/j.bmc.2004.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of Rho kinase inhibitors (I)

Abstract: Several structurally unrelated scaffolds of the Rho kinase inhibitor were designed using pharmacophore information obtained from the results of a high-throughput screening and structural information from a homology model of Rho kinase. A docking simulation using the ligand-binding pocket of the Rho kinase model helped to comprehensively understand and to predict the structure-activity relationship of the inhibitors. This understanding was useful for developing new Rho kinase inhibitors of higher potency and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 29 publications
1
57
0
Order By: Relevance
“…Compared to the other 491 human kinases investigated ROCK (ROCK-1 and ROCK-2) is unique with respect to the combination of the AGC characteristic residue Phe360 (in ROCK-1 corresponds to Phe327 in PKA, which has 37% sequence identity to ROCK) and mutations Ile82 (Leu49 in PKA), Met156 (Val123 in PKA), Ala215 (Thr183 in PKA), and Asp160 (Glu127 in PKA) (Breitenlechner et al, 2003;Takami et al, 2004). These residues are important shape determinants for the ATP-binding cavity of ROCK.…”
Section: Docking Azaindole 1 In a Rock-modelmentioning
confidence: 99%
“…Compared to the other 491 human kinases investigated ROCK (ROCK-1 and ROCK-2) is unique with respect to the combination of the AGC characteristic residue Phe360 (in ROCK-1 corresponds to Phe327 in PKA, which has 37% sequence identity to ROCK) and mutations Ile82 (Leu49 in PKA), Met156 (Val123 in PKA), Ala215 (Thr183 in PKA), and Asp160 (Glu127 in PKA) (Breitenlechner et al, 2003;Takami et al, 2004). These residues are important shape determinants for the ATP-binding cavity of ROCK.…”
Section: Docking Azaindole 1 In a Rock-modelmentioning
confidence: 99%
“…Trauger's report 18) suggested that S6-peptide is also one of selective substrates for ROCK, and conformed by Turner et al 16) The IC 50 of Y-27632 based on fluorescent S6-peptide in present study was similar to Turner's report, 16) which suggested the FP assay system is effective to determine ROCK activity. Takami et al 10) had successfully screened 69000 compounds based on SPA model, the substrate in their experiment also was S6-peptide.…”
Section: Fig 4 Activity Evaluation Of the Five Lead Compounds In Pcmentioning
confidence: 99%
“…According to Takami's report, 10) compounds, whose IC 50 is less than 3 mM, could be grouped to strong ROCK inhibitors. Present study set the standard to 10 mM in order to limit false negative.…”
Section: Fig 4 Activity Evaluation Of the Five Lead Compounds In Pcmentioning
confidence: 99%
“…Compounds such as analogues 4 and 5 [18] have been described by researchers from Kirin Brewery as potent ROCK inhibitors in vitro. GlaxoSmithKline disclosed two distinct ROCK inhibitor series, aminoA C H T U N G T R E N N U N G furazan-azabenzA C H T U N G T R E N N U N G imidazoles [19] and dihydropyridone indazole amides; [20] compounds 6 and 7 are shown as representative example, respectively.…”
Section: Introductionmentioning
confidence: 99%